Sex-related differences in the association between plasma fibrinogen and non-calcified or mixed coronary atherosclerotic plaques - Tiewei Li; Fang Wang; Rui Peng; Shengqiang Pei; Zhihui Hou; Bin Lu; Xiangfeng Cong; Xi Chen (Biology of Sex Differences, 2018)
Abstract Background Plasma fibrinogen (FIB) has been demonstrated to be a risk factor for cardiovascular disease. Patients with non-calcified plaque (NCP) or mix plaque (MP) have a higher risk of poor outcomes. However, the association between FIB and the presence of NCP or MP (NCP/MP) remains unclear, and if present, whether sex has any impact on this association remains unknown. The aim of this study was to investigate the role of FIB in predicting the presence of NCP/MP and evaluate whether sex has any impact on this association. Methods A total of 329 subjects were recruited, and the clinical and laboratory data were collected. Plasma FIB was detected by enzyme-linked immunosorbent assay. According to whether they had coronary atherosclerotic plaques and the characteristics of the most stenotic plaque, we divided them into three groups: no plaque (NP), calcified plaque (CP), and NCP/MP. Results Patients with NCP/MP had significantly higher FIB level in females, but not in males. Multiple logistic regression analysis showed that FIB was an independent risk factor for the presence of NCP/MP (odds ratio [OR] = 3.677, 95% CI 1.539–8.785, P = 0.003) in females. Receiver operating characteristic (ROC) curve analysis showed that the optimal cut-off value FIB for predicting the presence of NCP/MP was 3.41 g/L (area under curve [AUC] = 0.73, 95% CI 0.63–0.82, P <  0.001) in females. Conclusions FIB is independently associated with the presence of NCP/MP in females, but not in males. These results suggest that the potential significance of FIB-lowering regimens in females with NCP/MP.